The Regional Characteristics and Preservation of Chinese Folk Dance— A Case Study of the Gannan Tea-Picking Dance (Journal of Global Arts Studies, 2024)
Background: The regional characteristics and preservation of Chinese dance have gained increasing scholarly attention. As a representative local dance form with distinctive cultural value, the Gannan Tea-Picking Dance reflects the close relationship between regional culture and folk dance traditions. Objective: This paper aims to explore the regional characteristics and preservation issues of Chinese dance, focusing on the artistic features and cultural significance of the Gannan Tea-Picking Dance. Methods: Taking the Gannan Tea-Picking Dance as a case study, this research analyzes its historical origins, stylistic characteristics, and relationship with regional culture through literature review and cultural analysis, while also examining its current status of inheritance and preservation. Results: The study reveals that regional culture plays a crucial role in shaping the dance form, performance style, and artistic expression of the Gannan Tea-Picking Dance. At the same time, the dance currently faces challenges in inheritance, dissemination, and sustainable preservation. Conclusion: This paper proposes relevant suggestions to provide both scientific support and practical guidance for the sustainable development of the Gannan Tea-Picking Dance, emphasizing its important role in preserving regional culture and promoting the inheritance of traditional Chinese folk dance.
Keywords: Gannan Tea-Picking Dance; regional culture; cultural inheritance; intangible cultural heritage